Design, Synthesis, and Biological Evaluation of 2-Anilino-4-Triazolpyrimidine Derivatives as CDK4/HDACs Inhibitors - Wang S; Han S; Cheng W; Miao R; Li S; Tian X; Kan Q (Dove Medical Press, 2022)
Suhua Wang,1,2 Siyuan Han,1,2 Weiyan Cheng,1,2 Ruoyang Miao,1,2 Shasha Li,1,2 Xin Tian,1,2 Quancheng Kan1,2 1Department of Pharmacy, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, 450052, People's Republic of China; 2Henan Key Laboratory of Precision Clinical Pharmacy, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, 450052, People's Republic of ChinaCorrespondence: Xin Tian; Quancheng Kan, Email tianx@zzu.edu.cn; kanqc@zzu.edu.cnPurpose: To enhance the cytotoxicities of our obtained CDK4 inhibitors and get CDK4/HDACs inhibitors with potent enzymatic inhibitory and anti-proliferative activities.Methods: A series of novel CDK4/HDACs inhibitors were designed and synthesized by incorporating the HDAC pharmacophores (hydroxylamine or o-diaminoaniline) into the basic structure of our newly obtained 2-anilino-4-triazolpyrimidine based CDK4 inhibitors. The enzymatic inhibitory (HDAC1, CDK2, CDK4, and CDK6) activities and cytotoxicities of these compounds were evaluated. Moreover, HDAC isoforms inhibitory activity, cell cycle arrest assay, cell apoptosis analysis, cell migration, and cell colony formation assay were performed for the representative compound 11k.Results: Most of these compounds showed excellent HDAC1 inhibitory activities (IC50s: 0.68∼ 244.5 nM) and anti-proliferative activities against cancer cell lines. Some compounds displayed potent CDK4 inhibitory activities and a certain selectivity towards CDK2 and CDK6. Compound 11k exhibited potent enzymatic (CDK4: IC50=23.59 nM; HDAC1: IC50=61.11 nM; HDAC2: IC50=80.62 nM; HDAC6: IC50=45.33 nM) and anti-proliferative activities against H460, MDA-MB-468, HCT116, and HepG2 cell lines with IC50 values 1.20, 1.34, 2.07, and 2.66 μM, respectively. Further mechanistic studies revealed that compound 11k could arrest the cell cycle in G0/G1 phase and induce apoptosis in HCT116 and MDA-MB-468 cells. In addition, compound 11k significantly inhibited the migration and cell colony formation of H460 and HCT116 cells.Conclusion: This study suggested that the incorporation of the HDAC pharmacophore into CDK4 inhibitor scaffold to design CDK/HDAC inhibitors might be a tractable strategy to enhance the antitumor potency of compounds.Keywords: CDK4, HDAC, inhibitor, 2-anilino-4-triazolpyrimidine, cancer